Prenatal Isolated Congenital Diaphragmatic Hernia: A Rare Clinical Presentation of a GATA4 Pathogenic Variant - Tulonen, Nea; Tallus, Jussi; Kaprio, Heidi; Laine, Jukka; Mattila, Mirjami; Haanpää, Maria; Keskinen, Sini (SAGE Publications, 2026)
Congenital diaphragmatic hernia is a genetically heterogeneous condition with a developmental defect in the diaphragm. The GATA4 gene is essential for fetal heart development, and pathogenic GATA4 variants are a known cause of structural congenital heart diseases. Haploinsufficiency of GATA4 is also associated with diaphragmatic hernia. Pathogenic GATA4 sequence variants with isolated diaphragmatic hernia in the absence of congenital heart defects are extremely rare. Our report expands the phenotypic spectrum related to GATA4.We report a fetus with a prenatal isolated diaphragmatic hernia detected during a routine screening ultrasound. An autopsy of the fetus confirmed a large isolated posterolateral hernia, which affected the left lung volume significantly. Clinical exome sequencing revealed a novel heterozygous nonsense variant c.826C>T,p.(Gln276*) in the GATA4 gene, which was predicted to cause haploinsufficiency. The variant occurred de novo and was classified as pathogenic.The report presents a detailed clinical description of the fetus with ultrasound, MRI, and post-mortem pictures of a rare prenatal isolated diaphragmatic hernia related to a novel pathogenic GATA4 sequence variant. Prenatal ultrasound screening with further investigation by MRI and a comprehensive gene panel holds a key role in determining the prognosis of a fetus with a diaphragmatic hernia.